Peran Pembelajaran Pendidikan Lingkungan Sosial Dalam Pembentukan Sikap Peduli Lingkungan Peserta Didik - Asnita Nainggolan; Anggiat Sinurat; Tioner Purba; Ease Arent; Rima Meilitasari (Departement of Mathematics Education, 2023)
The role of the social environment has an important role in the formation of environmental care attitudes of students. The social environment is the family environment, school environment, and community environment. This study aims to determine the role of the family environment, school environment, and society in the formation of environmental care attitudes of students at SMA NEGERI 1 TARUTUNG. This study uses a descriptive qualitative research method. The research sample consisted of 25 students, 1 principal, 1 vice principal, 5 teachers, and 25 parents. The instruments in this study were observations, interviews, and documentation studies. Data analysis using analysis of data collection, data reduction, data presentation, drawing conclusions. The results of the study show that the family environment, school environment, and community play a significant role and contribute to the formation of students' environmental care attitudes.